2020
DOI: 10.3390/app10134677
|View full text |Cite
|
Sign up to set email alerts
|

Cryobiotechnology of Plants: A Hot Topic Not Only for Gene Banks

Abstract: Agriculture has always been an important part of human evolution. Traditionally, farming is changing and developing with regard to challenges it faces. The major challenges of modern agriculture are food and nutrition safety for the growing world population. Promoting species and genetic diversity in agriculture appears to be an important approach to dealing with those challenges. Gene banks all around the world play a crucial role in preserving plant genetic resources for future crop improvements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In 1997, Brison et al [ 54 ] reported the first successful eradication of Plum pox virus (PPV) from the infected shoot tips of a Prunus rootstock, using a vitrification method. Since then, shoot tip cryotherapy has been successfully applied to eradicate 37 viruses [ 52 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ], two viroids [ 163 ], two phytoplasmas [ 164 , 165 ], and one bacterium [ 166 ] in 31 plant species. To date, five phloem-limited grape viruses have been eradicated by shoot tip cryotherapy, including Grapevine fanleaf virus (GFLV), Grape virus A (GVA), Grapevine leafroll-associated virus-1,-2,-3 (GLRaV-1,2,3) [ 34 , 51 , 62 , 63 , 64 , 167 ] ( Table 2 ).…”
Section: Shoot Tip Cryotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, Brison et al [ 54 ] reported the first successful eradication of Plum pox virus (PPV) from the infected shoot tips of a Prunus rootstock, using a vitrification method. Since then, shoot tip cryotherapy has been successfully applied to eradicate 37 viruses [ 52 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ], two viroids [ 163 ], two phytoplasmas [ 164 , 165 ], and one bacterium [ 166 ] in 31 plant species. To date, five phloem-limited grape viruses have been eradicated by shoot tip cryotherapy, including Grapevine fanleaf virus (GFLV), Grape virus A (GVA), Grapevine leafroll-associated virus-1,-2,-3 (GLRaV-1,2,3) [ 34 , 51 , 62 , 63 , 64 , 167 ] ( Table 2 ).…”
Section: Shoot Tip Cryotherapymentioning
confidence: 99%
“…Relative to shoot tip culture or thermotherapy followed by shoot tip culture, shoot tip cryotherapy has the following advantages: cryotherapy yields pathogen-free plants at a high frequency; avoids the time-consuming excision of very small tissues, which requires skillful technicians; does require special equipment in addition to that typically available in a plant tissue culture laboratory. In summary, cryotherapy facilitates the treatment of a large number of samples quickly and simultaneously, reducing costs and making procedures shorter compared to thermotherapy followed by shoot tip culture [ 52 , 54 , 64 , 81 , 152 , 153 , 154 , 155 , 175 , 178 ].…”
Section: Shoot Tip Cryotherapymentioning
confidence: 99%
“…[ 74 ]. Further advantages and disadvantages of the cryotherapy method are very well summarized in many recent reviews [ 76 , 79 , 81 , 82 ].…”
Section: Shoot Tip Cryotherapymentioning
confidence: 99%
“…A cryopreserved collection may be used for the establishment of a safety backup for crops propagated clonally. An additional benefit of such backup, compared to the traditional seed bank, is that it can serve hundreds or even thousands of years and does not require regeneration after a few years of storage [ 38 ]. However, despite cryogenic storage having evident strategic merit, the resulting injuries from the cooling and rewarming cycles (affecting the membranes structure, cellular functions, and recovery potential) can cause unacceptable declines in the cell’s viability and regrowth of complete plants, which remains a major limiting factor [ 32 ].…”
Section: Importance and General Principles Of Cryopreservationmentioning
confidence: 99%